2019
DOI: 10.12659/msm.914538
|View full text |Cite|
|
Sign up to set email alerts
|

Improvement of Gut Microbiota by Inhibition of P38 Mitogen-Activated Protein Kinase (MAPK) Signaling Pathway in Rats with Severe Acute Pancreatitis

Abstract: Background Gut microbiota dysbiosis plays a key role in pathogenesis of severe acute pancreatitis (SAP). In this study, we explored the protective effects of the p38 MAPK inhibitor, SB203580, against gut inflammation and microbiota dysbiosis induced by pancreatic duct injection with 3.5% sodium taurocholate in an SAP rat model. Material/Methods Ninety male Sprague-Dawley rats were randomly assigned to sham-operated, SAP model, and SAP plus SB203580 groups (n=30/group). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 24 publications
(27 reference statements)
2
21
0
Order By: Relevance
“…19 Other studies in animal models also showed that improvements in the gut microbiota or supplementation with its metabolites ameliorated pancreatic injury by maintaining gut homeostasis. [20][21][22][23] Here, we observed that depletion of the gut microbiota reduced pancreatic damage and suppressed the systemic inflammatory response, while FMT reversed this process. This finding was consistent with previous studies that showed a protective effect of antibiotics on AP, and this protective effect was weakened after transplanting gut commensal bacteria.…”
Section: Discussionmentioning
confidence: 55%
“…19 Other studies in animal models also showed that improvements in the gut microbiota or supplementation with its metabolites ameliorated pancreatic injury by maintaining gut homeostasis. [20][21][22][23] Here, we observed that depletion of the gut microbiota reduced pancreatic damage and suppressed the systemic inflammatory response, while FMT reversed this process. This finding was consistent with previous studies that showed a protective effect of antibiotics on AP, and this protective effect was weakened after transplanting gut commensal bacteria.…”
Section: Discussionmentioning
confidence: 55%
“…Recent studies indicate that intestinal microbiota participate in the occurrence and development of pancreatitis [7,8]. Our group has previously reported dramatically changed intestinal microbiota in rats with pancreatitis, and we were able to improve the intestinal microbiota imbalance of theses rats with anti-inflammatory therapy [9]. Evidence also indicates that bile acids are involved in the development of AP, but the exact mechanisms underlying this association are unclear, especially in non-biliary pancreatitis [10].…”
Section: Introductionmentioning
confidence: 77%
“…Samples were analyzed by 16S rDNA gene sequencing, the details of which we have reported previously [ 9 ] . Operational taxonomic units (OTUs) that reached 97% similarity and Shannon index were used for α -diversity estimations.…”
Section: Analysis Of Intestinal Microbiotamentioning
confidence: 99%
“…In this study, modafinil treatment significantly reduces IL-6, TNF-α and CRP levels in the serum of AP rats, replying that modafinil might repress pro-inflammatory process to some extent. The studies have demonstrated that inflammation response in AP could be regulated by p38 MAPK pathway or microRNA, which implied that modafinil might also reduce inflammation through affecting aforementioned substance (Gu et al 2019;Wan et al 2019).…”
Section: Discussionmentioning
confidence: 99%